A national megastudy shows that email nudges to elementary school teachers boost student math achievement, particularly when personalized - Angela L. Duckworth; Ahra Ko; Katherine L. Milkman; Joseph S. Kay; Eugen Dimant; Dena M. Gromet; Aden Halpern; Youngwoo Jung; Madeline K. Paxson; Ramon A. Silvera Zumaran; Ron Berman; Ilana Brody; et al. (Proceedings of the National Academy of Sciences, 2025)
In response to the alarming recent decline in US math achievement, we conducted a national megastudy in which 140,461 elementary school teachers who collectively taught 2,992,027 students were randomly assigned to receive a variety of behaviorally informed email nudges aimed at improving students’ progress in math. Specifically, we partnered with the nonprofit educational platform Zearn Math to compare the impact of 15 different interventions with a reminder-only megastudy control condition. All 16 conditions entailed weekly emails delivered to teachers over 4-wk in the fall of 2021. The best-performing intervention, which encouraged teachers to log into Zearn Math for an updated report on how their students were doing that week, produced a 5.06% increase in students’ math progress (3.30% after accounting for the winner’s curse). In exploratory analyses, teachers who received any behaviorally informed email nudge (vs. a reminder-only megastudy control) saw their students’ math progress boosted by an average of 1.89% during the 4-wk intervention period; emails referencing personalized data (i.e., classroom-specific statistics) outperformed emails that did not by 2.26%. While small in size, these intervention effects were consistent across school socioeconomic status and school type (public, private, etc.) and, further, persisted in the 8-wk post-intervention period. Collectively, these findings underscore both how difficult it is to change behavior and the need for large-scale, rigorous, empirical research of the sort undertaken in this megastudy.